2017
DOI: 10.3389/fimmu.2017.01404
|View full text |Cite
|
Sign up to set email alerts
|

Janus-Faced Neutrophil Extracellular Traps in Periodontitis

Abstract: Periodontitis is characterized by PMN infiltration and formation of neutrophil extracellular traps (NETs). However, their functional role for periodontal health remains complex and partially understood. The main function of NETs appears to be evacuation of dental plaque pathogen-associated molecular patterns. The inability to produce NETs is concomitant with aggressive periodontitis. But in cases with exaggerated NET production, NETs are unable to maintain periodontal health and bystander damages occur. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 78 publications
1
31
0
2
Order By: Relevance
“…Neutrophils can also capture bacteria with neutrophil extracellular traps (NETs), which are web-like structures mainly consisting of decondensed chromatin and bactericidal proteins ( 22 , 23 ). Recent studies have shown that NETs are abundantly produced in periodontitis ( 24 , 25 ). During the process of NET activation and release (known as NETosis), DNA-bound histones are citrullinated by the human peptidylarginine deiminases, leading to a change in charge and decondensation of the DNA ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils can also capture bacteria with neutrophil extracellular traps (NETs), which are web-like structures mainly consisting of decondensed chromatin and bactericidal proteins ( 22 , 23 ). Recent studies have shown that NETs are abundantly produced in periodontitis ( 24 , 25 ). During the process of NET activation and release (known as NETosis), DNA-bound histones are citrullinated by the human peptidylarginine deiminases, leading to a change in charge and decondensation of the DNA ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…As we know, the formation of citrullinated proteins is catalyzed by peptidylarginine deiminase (PAD) enzymes. Porphyromonas gingivalis (P. gingivalis), an oral bacteria that is a crucial factor for periodontitis and express PAD and citrullinated enolase, can mediate citrullination of bacterial and host protein [89]. It has been shown that deletion of the bacterial PAD gene results in complete abrogation of protein citrullination [90].…”
Section: Parodontitis Nets and Anticitrulline Response In Ramentioning
confidence: 99%
“…Besides their role as a host defense mechanism, NETs play a pivotal role in non-infectious conditions, such as systemic lupus erythematosus ( 6 ), rheumatoid arthritis, cystic fibrosis ( 7 , 8 ), and psoriasis ( 9 ). They are also involved in other pathological processes, such as coagulation disorders, thrombosis ( 10 ), diabetes ( 11 , 12 ), atherosclerosis ( 13 ), vasculitis ( 14 ), wound healing ( 12 ), and periodontitis ( 15 , 16 ). Recently, several studies have investigated the role of NETs in tumors and reported their involvement in cancer immunoediting ( 3 ), progression ( 3 , 17 19 ), metastatic spread ( 20 ), and cancer associated thrombosis ( 20 ).…”
Section: Introductionmentioning
confidence: 99%